Análisis de las parrillas de programación de los canales de televisión de cobertura nacional del Ecuador, a un año de la Ley de Comunicación - Maldonado Vivanco, Juan Carlos (2015)
Television is one of the most widely accepted means in Ecuador and in turn the most influential audience. The Organic Law of Communication (LOC) adopted in June 2013, provides radical changes in the content of programming grids of Ecuadorian television channels. In this sense, this research develops a comparison of the evolution of programming grids before and after the adoption of the LOC and identifies the best broadcasters are adapting to legal and statutory requirements and also those that are in the process . The analysis was performed through Week methodology type and evaluates the following variables: type of program, origin (country of origin), duration in minutes and classification. Grills national television programming was analyzed: Teleamazonas, Ecuavisa, RTS, Canal UNO, ECTV, TC Television and TV Series; for 4 weeks, from 06h00 to 00h00, from 01 to 28 September 2014.